PENGARUH MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN, SOSIALISASI PAJAK, RELAKSASI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DALAM MENGGUNAKAN E-FILING SELAMA MASA PANDEMI - Sri Ayem; Aristo Tatag Staquf (Jurnal Akuntansi Dan Manajemen, 2022)
This study aims to examine the effect of modernizing the tax administration system, tax socialization, tax relaxation on taxpayer compliance in using e-filing during the COVID-19 pandemic on individual taxpayers in the city of Yogyakarta. To test the hypothesis used primary data. The data analysis technique used is the analysis by modernizing the tax administration system, tax socialization, tax relaxation as a variable (X) and taxpayer compliance as a variable (Y).. Tax relaxation has a positive effect on individual taxpayer compliance during the COVID-19 pandemic with a t-count value of 5.233 which is greater than the t-table value of 1.988 with a significance value of 0.000.